Double Surface Cracks Interaction on Cylindrical Rod Under Tensile and Torsional Loading - Awang, Muhamad Khairudin; M M Hamdan; Al Emran Ismail (Research Progress in Mechanical and Manufacturing Engineering, 2020)
The existence of cracks under loadings such as tensile and torsional loads is one of the factors that cause structures to experience failures. Further study regarding the effect of cracks has to be performed to analyze more about the severity of the defect on structures especially when it involves multiple cracks. Each crack configuration will emit different types of severity to the structures. This study aims to find the interaction between two identical surface cracks on a cylindrical rod under a combination of tensile and torsional loadings. The dimension for length and diameter of the cylinder has been set as 200 mm and 50 mm respectively. The analysis is simulated into a 3-D model using ANSYS Workbench Software where the meshing model and crack geometry is done by finite element analysis. There is no angular crack distance set for this study as both cracks are located parallel to each other. The distance between the interacting cracks is kept constant at 100 mm. The crack depth ratio used is 0.1 to 0.4 with the increment of 0.1 while for crack aspect ratio is 0.2 to 1.2 with the increment of 0.2. The stress intensity factor would be determined by the result of the simulation process. The value of stress intensity factor for single cracks and double cracks are applied in the formula of normalized stress intensity factor. The relation between stress intensity factor and interaction factor would be analyzed in this study.